Investigating the effects of RAW264.7 macrophages treated with melatonin on the erythroleukemia cell line K562 - masoumeh Ahanjan; meysam Abtahi Froushani; N.A Afzal Ahangaran (Journal of Advanced Biomedical Sciences, 2018)
Background & Objectives: Macrophages have a variety of functions and different phenotypes that are affected by the microenvironment. Due to the multiple functions, Melatonin can promote the cancer progression or cancer regression in relation to other factors. However, there is no information about the role of melatonin on the formation of macrophages in the tumor environment. The purpose of the present study is to evaluate the effects of melatonin treated RAW264.7 macrophages on the growth rate of erythroleukemia cell line K562. Materials & Methods: RAW264.7 cells were cultured in the 24-well plates at a density of 6 × 104 cells per well. After culturing for 24 h, the cells were treated for 24 h with melatonin at concentrations 0, 50, 75, 100, 150, 200 μmol/L. After removal of the supernatant, macrophages and K562 were co-cultured in 1:10 ratio. K562 vitality was then determined by MTT and NR assay. The rate of apoptosis in the cell population was evaluated by staining with acridine orange and ethidium bromide colors. Also, NO and MPO were measured in the supernatant of macrophages RAW264.7. Data were statistically analyzed using Kruskal-Wallis and Mann–Whitney U test (P<0.05). Results:  The growth rate and vitality of K562 cells co-cultured with melatonin-treated macrophages was increased at concentrations of 50 and 75 μmol/L. Nevertheless, at higher concentrations of melatonin, this process was reversed. The levels of MPO and NO were decreased by increasing concentrations of melatonin. Conclusion: These results indicated that treatment of macrophage with melatonin, especially at lower doses (50 and 75μmol/L) could remarkably increase the K562 viability and vitality.